Some issues about science and technology potential of The People’s Democracy Republic of Laos - Hai, Nguyen Hoang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
The potential of science and technology is an important foundation in the development of a nation’s science and technology. In order to have a basis for orienting the development of science and technology, many countries have organized surveys and statistics to assess the current state of S&T potentials, thereby having priority strategies to develop national S&T activities well suitable. In the ASEAN region, Lao PDR is a country that has made great efforts in promoting S&T potential. However, a review of international studies on Laos shows that specific information and data on the S&T potential of Laos are still relatively modest. With the support of colleagues at the Institute of Science and Technology Management, Ministry of Science and Technology of Laos, this article initially maps the picture of the S&T potential of Laos and at the same time points out some issues about the orientation of S&T development of Laos in the present time and in the future. Code: 21040101